Molecular Analysis of Mixed Endometrioid and Serous Adenocarcinoma of the Endometrium - Lawrenson, Kate (PLoS One, 2015)
BACKGROUND: The molecular biology and cellular origins of mixed type endometrial carcinomas (MT-ECs) are poorly understood, and a Type II component of 10 percent or less may confer poorer prognoses. METHODOLOGY/PRINCIPAL FINDINGS: We studied 10 cases of MT-EC (containing endometrioid and serous differentiation), 5 pure low-grade endometrioid adenocarcinoma (EAC) and 5 pure uterine serous carcinoma (USC). Endometrioid and serous components of the MT-ECs were macrodissected and the expression of 60 candidate genes compared between MT-EC, pure USC and pure EAC. We found that four genes were differentially expressed when MT-ECs were compared to pure low-grade EAC: CDKN2A (P = 0.006), H19 (P = 0.010), HOMER2 (P = 0.009) and TNNT1 (P = 0.006). Also while we found that even though MT-ECs closely resembled the molecular profiles of pure USCs, they also exhibit lower expression of PAX8 compared to all pure cases combined (P = 0.035). CONCLUSION: Our data suggest that MT-EC exhibits the closest molecular and epidemiological similarities to pure USC and supports clinical observations that suggest patients with MT-EC should receive the same treatment as patients with pure serous carcinoma. Novel specific markers of MT-EC could be of diagnostic utility and could represent novel therapeutic targets in the future.